2011
DOI: 10.1258/jtt.2011.110811
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of tele-education versus conventional lectures in wound care knowledge and skill acquisition

Abstract: We conducted a randomized controlled study to compare conventional lectures with tele-education for delivering wound care education. Education was delivered by the two methods simultaneously to two classes. Forty-eight paramedics received a live didactic presentation and 41 paramedics received the same lecture via videoconferencing. The participants were evaluated by a multiple-choice examination and a practical test of their wound closure skills. There were no significant differences in any category of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…20 The effectiveness of the learning through teleducation and its quality were similar to conventional methodologies of didactics. 21 …”
Section: Discussionmentioning
confidence: 99%
“…20 The effectiveness of the learning through teleducation and its quality were similar to conventional methodologies of didactics. 21 …”
Section: Discussionmentioning
confidence: 99%
“…While some authors have argued that various alternative teaching methods are superior to lectures, [68][69][70] many studies have demonstrated that these alternatives are merely equivalent or perhaps even inferior to didactic teaching. [71][72][73][74][75][76][77][78][79][80] Some educators believe that lectures by experts in specific areas of medicine may still have value, although some limited data suggest that expert guest speakers at grand rounds do not produce increased knowledge retention. 81 What Strategies Are Available to Enhance Didactic Learning Sessions Within EM Programs and How Should Their Success Be Measured?…”
Section: Consensus Statement On Simulation-based Medicalmentioning
confidence: 99%
“…[83][84][85] Shortening lectures may be a way to streamline the delivery of content through didactic formats without decreasing test performance. 86 Others have suggested that videoconferencing technology, 71,87 or learning from digitally archived lectures, 88 are at least as effective as live didactic presentations at delivering information, which may give educators additional flexibility for the times and locations of learning activities. Defining the content of traditional didactic learning sessions may be important when designing future research studies, specifically determining whether such learning activities would include case presentations, morbidity and mortality conferences, and grand rounds presentations, in addition to core educational content.…”
Section: Consensus Statement On Simulation-based Medicalmentioning
confidence: 99%
“… 5 The Young Doctor Project (YDP), therefore, is an initiative that involves the use of interactive teleducation, integrating the areas of health and education, to promote classroom experiences that foster knowledge construction and exchange among elementary, middle, and high school students. 6 7 The YDP is an excellent teaching methodology that enables health education promoting awareness of the role of each person as an active health agent in the community. 8 The project started in 2007 and since then has been used across the country in different regions and sectors, establishing a link between students of elementary, middle, and high school and teachers.…”
Section: Introductionmentioning
confidence: 99%